2020
DOI: 10.3390/ijerph18010037
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Road Traffic Injuries Involving Children in Three Central American Countries, 2012–2015

Abstract: Although motor vehicle collisions (MVCs) are a worldwide public health concern due to their high injury, mortality, and fatality rates, few studies have addressed the epidemiologic behavior of MVCs in Latin American youth. Thus, this study was aimed at describing and comparing the characteristics of MVCs involving 0 to 14-year-olds in Costa Rica, Guatemala, and Panama. A secondary aim was to estimate the crude MVC-related injury, fatality, and mortality rates and their trends over time. We conducted a descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A prior investigation on infant and childhood road safety in Panama revealed that road-related mortality in infants and children is an important health issue, with the largest percentage of fatal outcomes documented for children under the age of five. Globally, the average yearly motor-vehicle-collision-related fatality rate (per million people) for 0 to 14 year olds is 6, while in Latin America, it is 32 [ 26 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…A prior investigation on infant and childhood road safety in Panama revealed that road-related mortality in infants and children is an important health issue, with the largest percentage of fatal outcomes documented for children under the age of five. Globally, the average yearly motor-vehicle-collision-related fatality rate (per million people) for 0 to 14 year olds is 6, while in Latin America, it is 32 [ 26 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Research has shown that proper implementation of CRSs decreases fatalities among infants and children, as well as trauma magnitude and frequency, and therefore accident-related consequences and impairment in this highly susceptible group [ 156 , 157 , 158 , 159 , 160 ]. Although Costa Rica has enacted a regulation requiring the application of CRSs, Panama and Guatemala do not possess laws for CRSs that conform with worldwide requirements [ 26 ].…”
Section: Future Directions Regarding Child Pedestrian Motor Vehicle C...mentioning
confidence: 99%
“…Injuries to children receive considerable attention worldwide [1,[3][4][5]. Road traffi c injuries are the leading cause of death and disability not only among adults, but also among children [1,3,4,[6][7][8][9][10]. Taking into account the current Ukrainian legislation, road traffi c accidents are considered an emergency situation in Ukraine (clause 1.6 of article 2 of the Code of Civil Protection of Ukraine [11]).…”
Section: Introductionmentioning
confidence: 99%